Efficacy and toxicity of 8 day methotrexate/folinic acid regimen in the management of low risk gestational trophoblastic neoplasia: a prospective observational study - Subbaiah, Murali; Radhakrishnan, Sujithradevi; Dorairajan, Jayalakshmi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Gestational trophoblastic neoplasia (GTN) is a rare malignancy that arises from abnormal proliferation of trophoblastic cells. Low risk GTN responds well to single agent chemotherapy with good survival rate. Objective of the study was to assess the efficacy and toxicity of methotrexate chemotherapy in low risk GTN patients receiving 8-day methotrexate (MTX)/folinic acid (FA) regimen. A prospective observational study done in a tertiary care hospital in South India. Methods: This prospective observational study was conducted at a tertiary care hospital in south India between July 2015 and July 2018 and included 56 patients with low risk GTN treated with 8-day MTX/FA regimen. Results: Among the 56 patients treated, complete remission was achieved in 50 (89.3%). Molar pregnancy was the most common preceding pregnancy event (96.7%) and 63.3% of them developed GTN within 4 months of evacuation. Six non responders were treated with EMACO regimen and achieved complete remission. The most common toxicities were mucositis (46.4%) and neutropenia (17.8%). Overall survival of low risk GTN was 100% at the end of median follow up period of 14.4 months. Conclusions: For patients with low risk GTN, 8-day MTX/FA regimen is associated with a high rate of remission and low toxicity.